2011
DOI: 10.1542/peds.2010-2194
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Parental Communication About Sex: A Systematic Review

Abstract: CONTEXT: The relative effectiveness of interventions to improve parental communication with adolescents about sex is not known. OBJECTIVE:To compare the effectiveness and methodologic quality of interventions for improving parental communication with adolescents about sex. METHODS:We searched 6 databases: OVID/Medline, PsychInfo, ERIC, Cochrane Review, Communication and Mass Media, and the Cumulative Index to Nursing and Allied Health Literature. We included studies published between 1980 and July 2010 in peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 59 publications
3
96
0
8
Order By: Relevance
“…48 From a separate review covering 1980 through July 2010, mothers were the primary discussant in all interventions. 49 In reviewing the role of fathers in sexual health discussions, Kirkman et al 50 found that fathers recognized, by selfreport, that they need to share the role of communication about this topic with their teenagers but that they leave the conversation to the mothers more often than not. Although mothers can also effectively teach their sons about sexuality, 51 the relationship boys have with their fathers or other male role models plays a crucial role in their sexual health, including reducing sexual risk taking and delaying initiation of sexual intercourse, especially in those boys with a connection to their fathers, whether they live in the same home or not.…”
Section: In the Homementioning
confidence: 99%
“…48 From a separate review covering 1980 through July 2010, mothers were the primary discussant in all interventions. 49 In reviewing the role of fathers in sexual health discussions, Kirkman et al 50 found that fathers recognized, by selfreport, that they need to share the role of communication about this topic with their teenagers but that they leave the conversation to the mothers more often than not. Although mothers can also effectively teach their sons about sexuality, 51 the relationship boys have with their fathers or other male role models plays a crucial role in their sexual health, including reducing sexual risk taking and delaying initiation of sexual intercourse, especially in those boys with a connection to their fathers, whether they live in the same home or not.…”
Section: In the Homementioning
confidence: 99%
“…61,62 Teenagers who can recall a parent communicating with them about sex are more likely to report delaying sexual debut and increased condom and contraceptive use. [63][64][65] One element of the If I Were Jack theory of change involves increasing communication about UTP among parents and teens. First, the resource includes a homework task and materials to generate the communication from the child's perspective.…”
Section: Involving Parents Through Schools In Relation To Relationshimentioning
confidence: 99%
“…Resulta posible, por lo tanto, que las discrepancias que se han hallado entre padres e hijos sobre la frecuencia de comunicación sobre el tema se deban a ello. Se podrían llevar a cabo programas educativos en los que se forme a los padres en contenidos sobre sexualidad, ITS/VIH y en habilidades de comunicación para incrementar la frecuencia y calidad de la comunicación sobre sexo con sus hijos (Akers et al, 2011;Kajula et al, 2014;Miller et al, 2011;Poulsen et al, 2010) así como optimizar e incrementar como principales fuentes de información de los hijos a los padres y madres.…”
Section: Discussionunclassified
“…En el ámbito sexual, una mayor frecuencia de comunicación tendría como consecuencia que los adolescentes acudan a sus progenitores cuando necesiten información al respecto (Sales et al, 2008). Así, en una revisión reciente de estudios se concluyó que los padres que participaban en intervenciones centradas en la comunicación parental sobre el sexo, mejoraban en varios dominios de la comunicación como por ejemplo, la frecuencia, la calidad y las intenciones comunicativas (Akers, Holland, & Bost, 2011). Otros hallazgos apuntan a que una mayor comunicación entre padres e hijos adolescentes sobre sexualidad se asocia con el incremento de actitudes positivas hacia el uso del preservativo y, por tanto, con su uso más frecuente (Malcolm et al, 2012).…”
Section: Introductionunclassified